Environment Effect Treatments in PWR Whole-Core Pin-by-Pin Calculation - Zhang, Bin; Li, Yunzhao; Wu, Hongchun (Frontiers in Energy Research, 2021)
The environment effect arises when pin-cell homogenized parameters are generated with reflective boundary condition. To treat it in whore-core pin-by-pin calculation, two works are summarized in this paper. Firstly, by analyzing the relative errors of pin-cell homogenized group constantsand the relative importance of pin-cell discontinuity factors (PDF) in each group, the importance of the correction of the PDFs of thermal group is recognized. Secondly, the least-squares method for multivariate polynomial is utilized to functionalize the relation of the thermal-group PDFs and the core parameters including diffusion coefficient, removal cross section, neutron source and normalized surface flux. The C5G7 and KAIST benchmarks are employed to evaluate the performance of the PDF predication. Numerical results indicate its effectiveness in reducing the errors of eigenvalue and pin power, especially for the cases with the fuel pins located near the interface between different assemblies.